A microfluidically perfused three dimensional human liver model. (December 2015) - Rennert, Knut; Steinborn, Sandra; Gröger, Marko; Ungerböck, Birgit; Jank, Anne-Marie; Ehgartner, Josef; Nietzsche, Sandor; Dinger, Julia; Kiehntopf, Michael; Funke, Harald; Peters, Frank T.; Lupp, Amelie; et al.
Abstract: Within the liver, non-parenchymal cells (NPCs) are critically involved in the regulation of hepatocyte polarization and maintenance of metabolic function. We here report the establishment of a liver organoid that integrates NPCs in a vascular layer composed of endothelial cells and tissue macrophages and a hepatic layer comprising stellate cells co-cultured with hepatocytes. The three-dimensional liver organoid is embedded in a microfluidically perfused biochip that enables sufficient nutrition supply and resembles morphological aspects of the human liver sinusoid. It utilizes a suspended membrane as a cell substrate mimicking the space of Disse. Luminescence-based sensor spots were integrated into the chip to allow online measurement of cellular oxygen consumption. Application of microfluidic flow induces defined expression of ZO-1, transferrin, ASGPR-1 along with an increased expression of MRP-2 transporter protein within the liver organoids. Moreover, perfusion was accompanied by an increased hepatobiliary secretion of 5(6)-carboxy-2′, 7′-dichlorofluorescein and an enhanced formation of hepatocyte microvilli. From this we conclude that the perfused liver organoid shares relevant morphological and functional characteristics with the human liver and represents a new in vitro research tool to study human hepatocellular physiology at the cellular level under conditions close to the physiological situation.